Green Alert : a strategic public relations plan to increase recycling (in collaboration with SembVISY recycling) - Ho, Sang Jun (2008)
CommFusion is a group of four undergraduates working in alliance with SembVISY Recycling (SVR), a subsidiary company of SembCorp Environmental Management. The Green Alert project aims to accomplish the communication goals and objectives of SVR through a combination of public relations tools. It embodies CommFusion’s operative philosophy, which involves integrating various communication tools with an injection of ingenuity. This report describes the key strategies and tools used in the campaign.